Crashworthy Examination of a Newly Proposed Impact Attenuator Design: Experimental Testing and Numerical Analysis. (24th September 2021) - Prasetya, Laksmana Widi; Prabowo, Aditya Rio; Ubaidillah, Ubaidillah; Hadi, Syamsul; Hidajat, Raymundus Lulus Lambang Govinda; Tuswan, Tuswan; Adiputra, Ristiyanto
Abstract : The impact attenuator is a safety vehicle system designed to absorb the kinetic energy from a collision that is converted into deformation and ensures the deceleration level acting on the human body remains low. In this paper, we propose that the impact attenuator be fabricated with used cans, which are easy to obtain. Compared to fabricating cylinders through machining and other production processes using new material, the application of used cans may reduce production costs by approximately IDR 500, 000 (USD 34.50) for one attenuator structure, while the attenuator still meets the weight criterion, i.e., it has to be light to improve acceleration and fuel efficiency. As a type of metal waste product, food cans are often fabricated from aluminum and other metal alloys. These products are widely used in our lives; if they are not recycled, they can potentially pollute the environment as waste. Given these problems and considering the use of environmentally friendly materials, lightweight used cans were chosen as materials for the proposed impact attenuator design. In the initial study, the verification and validation tests of the impact attenuator shell and used cans show good agreement between the numerical and experimental impact tests. The proposed impact attenuator design under the predetermined parameters showed that used cans of aluminum 6063 series can be recommended as an alternative material in this system.